The role of forestry sciences in combating climate change and advancing sustainable development goals - Raman, Raghu; Manalil, Sudheesh; Dénes, Dávid Lóránt; Nedungadi, Prema (Frontiers in Forests and Global Change, 2024)
As we face the threat of ecological disasters, forests have become key areas in combating climate change, emphasizing the crucial role of forestry sciences in driving efforts to protect our planet, aligning with the UN Sustainable Development Goals (SDGs). This study systematically examines the contribution of forestry science research to the SDGs through a multidisciplinary lens, highlighting its pivotal role in advancing global sustainability. Employing the PRISMA protocol, we identified and analyzed a corpus of 39,841 publications since the adoption of the SDGs in 2015, focusing on the intersection of the forestry sciences with the SDGs. Our findings reveal a significant emphasis on SDG 15 (Life on Land) and SDG 13 (Climate Action), underscoring the forestry sector's critical contributions to biodiversity conservation, climate change mitigation, and ecosystem services. The research underscores the interdisciplinary nature of forestry sciences, with substantial interactions among SDGs, as evidenced by network and keyword co-occurrence analyses. These analyses identify thematic clusters around ecological and environmental sustainability, sustainable energy and industry, and social development and urban planning, demonstrating the diverse ways in which forestry research intersects with and supports the SDGs. The study identifies areas of strong contribution and potential gaps where future research could further align with global sustainability objectives. Recommendations include future research directions such as integrating advanced remote sensing technologies and AI-driven analytics, exploring the socioeconomic impacts of forest-based livelihoods, and investigating innovative reforestation techniques. Additionally, programmatic activities should focus on strengthening urban forestry initiatives, prioritizing ecological sustainability, leveraging forests for sustainable energy, enhancing interdisciplinary cooperation, engaging communities, and improving governance to ensure that forestry sciences continue to contribute effectively to the SDGs and address future challenges in global well-being and sustainability.